Simultaneous measurement of the ratio R=B(t --> Wb)/B(t --> Wq) and the top-quark pair production cross section with the D0 detector at sqrt(s) = 1.96 TeV. - Abazov, V; Abbott, B; Abolins, M; Acharya, B; Adams, M; Adams, T; Aguilo, E; Ahn, S; Ahsan, M; Alexeev, G; Alkhazov, G; Alton, A; et al. (2008)
We present the first simultaneous measurement of the ratio of branching fractions, R=B(t --> Wb)/B(t --> Wq), with q being a d, s, or b quark, and the top-quark pair production cross section sigma(tt[over]) in the lepton plus jets channel using 0.9 fb(-1) of pp[over] collision data at sqrt(s)=1.96 TeV collected with the D0 detector. We extract R and sigma(tt[over]) by analyzing samples of events with 0, 1, and > or =2 identified b jets. We measure R=0.97(+0.09)/(-0.08)(stat+syst) and sigma(tt[over])=8.18(+0.09)(-0.84)(stat+syst) +/- 0.50(lumi) pb, in agreement with the standard model prediction.